The Role of the Darul Rahman Assembly in Building the Role of Mothers in Batoh Villagebuilding - Khamisah (MANDAILING GLOBAL EDUKASIA, 2024)
The role of the Darul Rahman Council in Building the Mothers in Bathoh village. The purpose of this research is to find out the extent of the role of the existence of Majelis Darul Rahman in the effort to educate mothers either individually or collectively/community that leads to social activities in Batoh Village, as well as wanting to know the response of the women of Batoh Village about the existence of Majelis Darul Rahman. In this research, the author uses library research (Library Research) and Field Research (Field Research) methods by using observation, interview, and questionnaire techniques. The results of research in the field show that the respondents consisting of mothers aged 30 to 60 years, totaling 58 people, divided into 86% who assessed that the Darul Rahman assembly played a role and was useful in the education of Islamic and Social Social teachings for mothers/women in Village Batoh. And there are 14% of other mothers (respondents) who gave a